RNA-directed off/on switch of RNase H activity using boronic ester formation. Issue 38 (19th September 2017) - Reverte, Maëva; Barvik, Ivan; Vasseur, Jean-Jacques; Smietana, Michael
Abstract : A new concept to modulate RNase H activity is presented based on the boronic acid/boronate switch. Abstract : RNase H is a non-specific endonuclease which degrades selectively the RNA strand in DNA/RNA duplexes. We demonstrate in the present study that 5′-boronic acid modified oligonucleotides hybridized to a RNA target sequence converts RNase H to an inactivated enzyme complex. The dynamic formation of a boronate ester upon addition of a diol moiety disrupts the enzyme-inhibitor complex and reactivates RNase H. Moreover, we show that reactivation of RNase H function can also be engineered through short RNA trimers inputs that fashion RNase H from a non-specific DNA-guided enzyme into an informational and programmable RNA-guided one. Examples of programmable RNA recognition and cleavage illustrate the potential of this new stimuli-responsive system.